Circulating interleukin-38 concentrations in healthy adults - Teufel, Lisa U.; de Graaf, Dennis M.; Netea, Mihai G.; Dinarello, Charles A.; Joosten, Leo A. B.; Arts, Rob J. W. (Frontiers in Immunology, 2022)
Interleukin (IL)-38 is the latest discovered member of the interleukin-1 family, which has anti-inflammatory properties similar to IL-36Ra. Several studies compared circulating IL-38 concentrations in healthy and diseased populations to characterize its role in both auto-immune and inflammatory pathologies, with both higher and lower concentrations being associated with certain diseases. However, in order to use IL-38 as a biomarker, a reference range in healthy adults is needed. To establish a reference IL-38 circulating concentration, accessible data from 25 eligible studies with IL-38 concentrations in healthy adults was collected. To validate the values found in literature, we measured IL-38 concentrations by enzyme-linked immunosorbent assay (ELISA) in several cohorts from our own institute. Additionally, the effect of blood collection techniques, freeze thawing cycles, and hemolysis on IL-38 measurements was assessed. To evaluate the importance of the genetic background of individuals as confounding factor of IL-38 synthesis, we used publicly available eQTL databases with matched data on allele frequencies in individuals of different ethnicities. Mean IL-38 concentrations in the various studies were weighted by their corresponding sample size, resulting in a weighted mean, and weighted upper and lower limits were calculated by mean ± 2 SD. Differences of over 10.000-fold were found in the weighted means between studies, which could not be attributed to the blood collection method or assessment of IL-38 in plasma or serum. Although IL-38 concentrations were markedly higher in Chinese then in European population studies, we could not show an association with the genetic background. From our analysis, a reference range for circulating IL-38 in healthy adults could thus not yet be established.